Advances in Battery Technologies for Next-Generation Energy Storage Systems - Sebbagh, Toufik; Manfo, Theodore Azemtsop; Şahin, Mustafa Ergin (MDPI, 2026)
Advancements in energy storage systems (ESS) are important to attaining a sustainable and resilient energy future. Despite significant advancements in battery technologies, including lithium-ion, sodium-ion, and redox flow batteries, numerous problems remain. These include low energy density, thermal instability, resource scarcity, high lifecycle costs, and ineffective recycling methods. Furthermore, the complexity of connecting battery systems to the grid while maintaining operational safety creates further impediments to implementation. Recent advancements, such as hybrid energy storage systems (HESS), better battery chemistries, and intelligent modeling tools based on MATLAB/Simulink R2025b, have shown promise in terms of performance, cost reduction, and more effective energy management. However, the scalability, recyclability, and real-world applicability of these systems require further exploration. The goal here is to provide a comprehensive overview of current and emerging battery technologies, focusing on technical performance, environmental sustainability, lifecycle cost modeling, and grid compatibility. This comprises a techno-economic study that employs process-based cost modeling (PBCM) and leveled cost of storage (LCOS), a thorough examination of green battery chemistries, and system-level modeling of battery and hybrid configurations. The study seeks to provide academics and stakeholders with a comprehensive framework that considers both the innovations and limitations of current ESS technologies in the context of global decarbonization targets.
Keywords: energy storage systems; battery technologies; green batteries; grid integration; scalability; cost; fi=Sähkötekniikka|en=Electrical Engineering|